Essential, fragile, and invisible community food infrastructure: The role of urban governments in the United States. (August 2021) - Clark, Jill K.; Conley, Brian; Raja, Samina
Highlights: National surveys shows that US urban governments utilize a range of policy tools. Domains of production and retail and food service receive more attention. Domain of middle infrastructure receives less attention. Middle infrastructure diversifies and builds resiliency through intermediated markets. Policy tools may be overregulating and underinvesting in food systems. Abstract: Community advocates and some scholars have argued that metropolitan food systems are central yet fragile food infrastructure. While recent events have suddenly laid this bare for many, it has been a matter of long-time concern to community advocates and scholars alike. Until recently, much of the food system has remained invisible to subnational policy makers. Within the past decade, an increasing number of urban local governments are heeding persistent calls from advocates and scholars to address the sustainability of metropolitan food systems in the United States. This paper provides a national overview of how urban local governments are engaging in policy for food systems (production, middle infrastructure, and retail and food service) across the United States. Results of a national survey of urban planners suggest that food systems policy is gaining attention, but progress needs to be made. While urban governments are prioritizing retail and food service and food production (both visible on the landscape), less attention is paid to the middle infrastructure that helps build self-reliance and resiliency by connecting production with consumption and building larger markets. Results also suggest that policy tools used by local governments are overregulating and underinvesting in food systems. Finally, the role of local governments supporting essential food system workers through planning and policy is raised.